A Comparison of the Center of Pressure Trajectory Between Dynamic Response Prosthetic Feet Having Different Ankle Designs. Issue 1 (January 2022) - Agrawal, Vibhor; Gaunaurd, Ignacio; Kim, Kyoung Jae; Bennett, Christopher; Gailey, Robert
ABSTRACT: Introduction: Commercially available dynamic response (DR) prosthetic feet have unique ankle designs, which provide different degrees of ankle motion. Differences in ankle motion between the prosthetic and anatomical foot creates an asymmetry in the locomotor system and affects its functions of shock absorption, progression, and stabilization. Ankle motion during gait can be assessed by quantifying the center of pressure (CoP) movement during the stance period of gait. Although previous studies have compared gait parameters between DR and non-DR feet, no studies have examined difference in CoP trajectories among common designs of DR feet. Methods: LP-Variflex, Talux, and Variflex prosthetic feet were used as test feet to represent the common DR feet, that is, low-profile (LP), multi-axial (MX), and J-shaped (JS) ankle designs, respectively. Five subjects with unilateral transtibial amputation (TTA), six subjects with unilateral transfemoral amputation (TFA), and three healthy controls participated in the study. Subjects were prosthetic users for at least 18 months and were classified as K-level 3 or K-level 4 functional level. Each subject received standardized functional prosthetic gait training and accommodation with each test foot. For data collection, subjects walked on level ground using standardized shoes and CoP data were collected using in-sole sensors. The testing order of feet was randomized. The A-P and M-L location of CoP was determined at the following gait phases: initial contact (2% of gait cycle), early midstance (15% of gait cycle), terminal stance (35% of gait cycle), preswing (50% of gait cycle), and before toe-off (60% of gait cycle). The maximum A-P and M-L CoP excursion was also calculated. The A-P displacement of the CoP was normalized to the foot length, and the M-L displacement was normalized to the foot width. Analysis of variance was used to calculate differences in CoP between test feet, and a comparison-wise alpha of P < 0.1 was considered as significant. Results: In the TTA group, there was a significant difference between feet in A-P CoP location during early midstance (15% gait cycle). For the MX foot, the CoP was located at 21.3% ± 3.1% of the foot length, which was significantly greater than the LP and JS feet (15.6% ± 2% and 14.1% ± 3.4% foot length, respectively). During the period from terminal stance to toe-off (35%–60% gait cycle), the split keel design of JS and LP feet had greater M-L movement compared with that of the MX foot. In the TFA group, there were no differences in CoP trajectory between test feet. The maximum A-P excursion for all prosthetic feet was significantly greater than control subjects (80.4% ± 0.5% and 69.1% ± 2.7% foot length, respectively). The maximum M-L excursion for all prosthetic feet was significantly lesser than control subjects (14% ± 3.7% and 26.2% ± 3.7% foot width, respectively). Conclusions: Differences in ankle design among different DR prosthetic feet can influence the asymmetry and functions of the locomotor system. In the TTA group, the MX foot resulted in a faster transition from initial contact to midstance, compared with the JS and LP feet. The split keel design of JS and LP feet closely mimicked the motion of the anatomical foot in late-stance period and provided controlled weight transfer from the prosthetic limb to the intact limb. In the TFA group, ankle design did not have a significant effect on CoP movement. All prosthetic feet had greater A-P CoP excursion and lower M-L excursion compared with the anatomical foot. Additional studies investigating the effects of DR foot/ankle designs on distinct functions of the locomotor system are needed to guide prosthetic foot prescription.